2018
DOI: 10.1002/pbc.27408
|View full text |Cite
|
Sign up to set email alerts
|

Managing local‐regional failure in children with high‐risk neuroblastoma: A single institution experience

Abstract: Background: Intensification of systemic therapy for high-risk neuroblastoma (HRNB) has resulted in improved local control and overall survival leaving potential for de-escalation of primary site radiotherapy. The utility of primary site de-escalation should be evaluated in the context of potential for successful local-regional salvage. We evaluated salvage strategies and outcomes in HRNB patients with local-regional recurrence as a component of first failure. Methods: Twenty of 89 patients with HRNB experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…So far, only a few studies investigated irradiation for local or metastatic recurrence. Dove et al reported on a cohort of 20 HR NB patients treated for loco-regional relapse [ 14 ]. Ten of these twenty patients received RT with a median total dose of 27 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only a few studies investigated irradiation for local or metastatic recurrence. Dove et al reported on a cohort of 20 HR NB patients treated for loco-regional relapse [ 14 ]. Ten of these twenty patients received RT with a median total dose of 27 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…HDRT delivered as Stereotactic Body Radiation Therapy (SBRT), Stereotactic Radiosurgery (SRS) or Intraoperative Radiation Therapy (IORT) is increasingly being used in pediatric cancers [ [7] , [8] , [9] ]. HDRT improves the outcome for several high-risk neuroblastoma patients [ 10 , 11 ]. Given these advances there is great interest in immunotherapy in neuroblastoma, used alone or in combination with HDRT, to improve patient outcome.…”
Section: Introductionmentioning
confidence: 99%